Mineralogical, petrographic and physical-mechanical study of Roman construction materials from the Maritime Theatre of Hadrian's Villa (Rome, Italy). (October 2018) - Columbu, S.; Lisci, C.; Sitzia, F.; Lorenzetti, G.; Lezzerini, M.; Pagnotta, S.; Raneri, S.; Legnaioli, S.; Palleschi, V.; Gallello, G.; Adembri, B.
Highlights: Maritime Theatre building respects the constructive technologies of Roman times. Basalt-scoria/rare cocciopesto aggregate gives pozzolanic characteristics to mortars. Mixing proportions of aggregate/binder are related to mortar's function in masonry. Hydration-dehydration/crystallization of gypsum/ettringite produces physical decay. Roman wall paintings consists of two different layers: hematite and Egyptian Blue Abstract: This paper presents the study of various Roman materials used in the construction of the Maritime Theatre, one of the main buildings in the Hadrian's Villa complex, a designated UNESCO World Heritage Site located in Tivoli (Rome, Italy), dating to the first half of the II century A.D. The plaster layers ( arriccio and intonachino ) and overlying original Roman paintings that form the concave wall of the portico as well as some bedding mortars of the pyramidal stone elements ( i.e. cubilia ) of the circular masonry have been studied in particular. In addition, the acid volcanic rocks of the cubilia have been investigated, aiming to understand their state of alteration and geological origin. By mineralogical-petrographic microscopy (OM), diffractometry (XRPD), Raman spectroscopy, Point Load Tests (PLT), helium pycnometry, and particle size analysis, the composition and granulometric distribution of the aggregate, type and characteristics of the binder, and various physical-mechanical properties (density, porosity, water absorption, imbibition and saturation indices, mechanical resistance) of mortars and stones were defined. In addition, through digital image analysis of thin sections, the binder/aggregate ratio and some geometric characteristics of the aggregates ( e.g. circularity) were determined. The research aims to improve the knowledge of the constructive technologies of the Maritime Theatre through the analysis of its materials.